Reformasi Hukum Perwalian Anak dalam Kasus Perceraian: Antara Kepentingan Anak dan Hak Orang Tua - muh ihsanudin (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2024)
Child custody arrangements in divorce cases remain a critical issue in family law, often sparking disputes between parents while potentially neglecting the best interests of the child. This study examines the reform of child custody laws in Indonesia by balancing the child’s best interests with parental rights, using a normative qualitative approach grounded in Islamic law and Indonesia's national legal framework. It explores the principles underlying custody decisions, particularly the alignment of existing laws with Islamic jurisprudence and international conventions such as the Convention on the Rights of the Child (CRC). The findings indicate that while Indonesian legal provisions prioritize the child’s welfare, implementation challenges persist, particularly in balancing parental rights and addressing gender biases in custody decisions. The study highlights the need for legal reforms to enhance clarity, consistency, and fairness in custody arrangements, emphasizing the integration of Islamic legal principles and global best practices to safeguard children’s rights. This article concludes by offering recommendations for a comprehensive reform of custody laws that not only uphold the best interests of the child but also ensure equitable consideration of parental roles. These reforms aim to bridge the gap between religious principles, national legal mandates, and international human rights standards in addressing custody disputes post-divorce.